Acrolein Can Cause Cardiovascular Disease: A Review - Henning, Robert J.; Johnson, Giffe T.; Coyle, Jayme P.; Harbison, Raymond D. (Cardiovascular toxicology, 2017)
Acrolein is a highly reactive unsaturated aldehyde that is formed during the burning of gasoline and diesel fuels, cigarettes, woods and plastics. In addition, acrolein is generated during the cooking or frying of food with fats or oils. Acrolein is also used in the synthesis of many organic chemicals and as a biocide in agricultural and industrial water supply systems. The total emissions of acrolein in the United States from all sources are estimated to be 62,660 tons/year. Acrolein is classified by the Environmental Protection Agency as a high-priority air and water toxicant. Acrolein can exert toxic effects following inhalation, ingestion, and dermal exposures that are dose dependent. Cardiovascular tissues are particularly sensitive to the toxic effects of acrolein based primarily on in vitro and in vivo studies. Acrolein can generate free oxygen radical stress in the heart, decrease endothelial nitric oxide synthase phosphorylation and nitric oxide formation, form cytoplasmic and nuclear protein adducts with myocyte and vascular endothelial cell proteins and cause vasospasm. In this manner, chronic exposure to acrolein can cause myocyte dysfunction, myocyte necrosis and apoptosis and ultimately lead to cardiomyopathy and cardiac failure. Epidemiological studies of acrolein exposure and toxicity should be developed and treatment strategies devised that prevent or significantly limit acrolein cardiovascular toxicity.